Janus organic semiconductor nanoparticles prepared by simple nanoprecipitation. (December 2022) - Holmes, A.; Laval, H.; Schmutz, M.; Blanc, S.; Allouche, J.; Watts, B.; Wantz, G.; Holmes, N.P.; Hirakawa, K.; Deniau, E.; Chambon, S.; Lartigau-Dagron, C.; et al.
Abstract: Nanoparticles (NPs) of donor–acceptor organic semiconductors are produced by a one-step nanoprecipitation with Janus morphology. Electron donor P3HT was blended with electron acceptor PC61 BM in tetrahydrofuran and then precipitated in water, first with surfactant and second without surfactant. Cryogenic transmission electron microscopy reveals an internal Janus structure at high magnification, for NPs which have, in the past, been reported to have a molecularly intermixed morphology. Synchrotron-based scanning transmission X-ray microscopy confirmed the segregation of the organic semiconductors and photoluminescence experiments showed an efficient electron transfer from P3HT to PC61 BM. Organic field effect transistors were fabricated with these Janus NPs and showed that the positive charges can be efficiently transported through thin films. This behavior proves that the NPs possess an electron-accepting face (the PC61 BM face) able to transport electrons and a hole-accepting face (the P3HT face) for the conduction of holes. Finally, the deposition of silver via the photoreduction of a silver salt (AgNO3(aq) ) was demonstrated, as a proof of concept. These experiments show the potential of the Janus NPs for photovoltaics but also photocatalytic reactions in which reduction and oxidation reactions can occur at opposite sides of the nanoreactor (the individual Janus NPs). Graphical abstract: Image 1 Highlights: Janus Particles are produced from the nanoprecipitation of organic semiconducting materials. All donor absorption is transferred to the acceptor. Charge transport has been confirmed by building OFET. Photodeposition of Silver metal has been performed on the organic nanoparticles to prove their potential for Photocatalysis.